PENGEMBANGAN ASPEK PEMASARAN USAHA KOPI BU TIANI DI DESA SUMBERMANJING WETAN - Novi Puji Lestari; Fika Fitriasari; Mochamad Rofik (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2021)
The purpose of this service is to increase the added value of Argotirto coffee in the Sumbermanjing Wetan sub-district, Malang Regency. After going through several phases, this empowerment finally resulted in the ground coffee brand